(untitled) (Journal of Plant Disease Sciences, 2019)
Collar rot of chilli (Capsicum annuum L.)caused by Sclerotium rolfsii Sacc.is currently occurring in chilli growing areas of Marathwada region in India. Cultural and morphological variability of nine isolates of S. rolfsii, collected from three agroclimatic zone consisting nine districts of Marathwada region of Maharashtra, India were studied. Out of nine isolates tested for their cultural and morphological variations, most of them were observed with raised colony with smooth margin. Based on growth rate, they were categorized into three groups such as moderate, good and excellent growing. Number of sclerotia, size of sclerotia and test weight of 100 sclerotia also varied among isolates substantially. Mostly dark to light brown sclerotia was observed for the isolates.Significant variability with reference to mycelial and sclerotial charactersacross isolates of S.rolfsii, isolated from different locations of Marathwada region of Maharashtra was observed.